Synthesis and Ex Vivo Trans-Corneal Permeation of Penetratin Analogues as Ophthalmic Carriers: Preliminary Results - Silvia Pescina; Marina Sala; Maria Carmina Scala; Patrizia Santi; Cristina Padula; Pietro Campiglia; Carmine Ostacolo; Sara Nicoli (MDPI AG, 2020)
Among enhancing strategies proposed in ocular drug delivery, a rising interest is directed to cell penetrating peptides (CPPs), amino acid short sequences primarily known for their intrinsic ability to cell internalization and, by extension, to cross biological barriers. In fact, CPPs may be considered as carrier for delivering therapeutic agents across biological membranes, including ocular tissues. Several CPPs have been proposed in ophthalmic delivery, and, among them, penetratin (PNT), a 16-amino acids natural peptide, stands out. Therefore, we describe the synthesis via the mimotopic approach of short fluorescently labeled analogues of both PNT and its reversed sequence PNT-R. Their ability to cross ocular membranes was checked ex vivo using freshly explanted porcine cornea. Furthermore, some sequences were studied by circular dichroism. Despite the hydrophilic nature and the relatively high molecular weight (approx. 1.6 kDa), all analogues showed a not negligible trans-corneal diffusion, indicating a partial preservation of penetration activity, even if no sequences reached the noteworthy ability of PNT. It was not possible to find a correlation between structure and corneal penetration ability, and further studies, exploring peptides distribution within corneal layers, for example using imaging techniques, deserve to be performed to figure out a possible difference in intracellular delivery.